2022
DOI: 10.3390/ijerph19041952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Benefit on Vitamin D Supplementation Intention: A Theory of Planned Behaviour Perspective

Abstract: There are many factors that affect vitamin D supplementation, including those from the theory of planned behaviour (TPB); however, how the perceived benefit acts in the model remains unknown. In the current study, we tested the efficacy of the TPB and the impacts of the perceived benefit (PBE) in the model. The subjects were 287 customers who purchased vitD from pharmacies in major cities in Taiwan. A structured questionnaire was used to collect the data. t-tests, analysis of variance (ANOVA), regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 71 publications
4
9
0
Order By: Relevance
“…However, the relationship was not as strong as that between subjective norms and purchase intention. Nonetheless, the results suggested that the greater the sense of control, the greater millennials' purchase intention, confirming the findings of El Khoury et al (2021) and Chen, Chao and Chu (2022).…”
Section: Perceived Behavioural Controlsupporting
confidence: 79%
See 2 more Smart Citations
“…However, the relationship was not as strong as that between subjective norms and purchase intention. Nonetheless, the results suggested that the greater the sense of control, the greater millennials' purchase intention, confirming the findings of El Khoury et al (2021) and Chen, Chao and Chu (2022).…”
Section: Perceived Behavioural Controlsupporting
confidence: 79%
“…Subjective norms reflect how consumers perceive the opinion of significant others, such as close friends, family, or colleagues, about a behaviour (Ajzen, 1991;Chen,…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…The study has clinical merits especially among OW and OB individuals since they are more susceptible to VD deficiency. Proper knowledge of VD dietary sources may favorably affect the individual’s intention to correct VD status and perceived benefits without consuming the added calories that goes along with these foods [ 28 ]. In the present study, the majority of the participants have good knowledge about VD independent of BMI status.…”
Section: Discussionmentioning
confidence: 99%
“…A structural educational program adopting healthy behavior interventions could improve women's knowledge and prevent VDI in Egypt [29]. Chen et al analyzed 287 Taiwanese individuals who purchased vitamin D from pharmacies and found that the perceived bene t was linked to the intention of vitamin D supplementation [30]. Healthrelated quality of life (HRQoL), an individual's self-reported overall sense of well-being based on subjective physical, social, and psychological functioning, has become an essential assessment outcome for healthcare provided to those with chronic illness [14].…”
Section: Introductionmentioning
confidence: 99%